2009
DOI: 10.1037/a0015468
|View full text |Cite
|
Sign up to set email alerts
|

Do Research Literatures Give Correct Answers?

Abstract: The rationale for insisting on properly designed studies is to ensure the construction of research literatures that are not influenced by biases of any sort. Once a literature is established, however, whatever answers it gives (usually via meta-analysis) are accepted as valid. The results of our favored statistical techniques are understood best when significant relationships are present while the meaning of null results are unclear. Thus, significant findings are more likely to be published. This file drawer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…Potentially problematic practices include selective reporting, selective analysis, and insufficient specification of the conditions necessary or sufficient to obtain the results (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). We were inspired to address the gap in direct empirical evidence about reproducibility.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Potentially problematic practices include selective reporting, selective analysis, and insufficient specification of the conditions necessary or sufficient to obtain the results (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). We were inspired to address the gap in direct empirical evidence about reproducibility.…”
Section: Resultsmentioning
confidence: 98%
“…Concerns about reproducibility are widespread across disciplines (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Reproducibility is not well understood because the incentives for individual scientists prioritize novelty over replication (20).…”
Section: Implications and Limitationsmentioning
confidence: 99%
“…Several factors relating to the replication crisis have recently been examined, including the arbitrary inclusion of covariates and selective adjustment of sample size (Simmons, Nelson, & Simonsohn, 2011), the different and at times improper ways of handling outliers (Bakker & Wicherts, 2014), and the pervasive “file-drawer” problem affecting the field as a whole (Howard et al, 2009). The importance of addressing the replication crisis is evident.…”
mentioning
confidence: 99%
“…Furthermore, Kromrey and Rendina-Gobioff [41] concluded that current statistical methods to account for publication bias may fail to control Type I error rates or lack sufficient power. Therefore, Howard et al [42] proposed a different way of addressing the file drawer problem using the example of the psychotherapy efficacy literature. Rather than correcting for bias statistically, they suggested performing a new mini-literature review meta-analysis of all their new studies and whether the results approached the value of a meta-analysis obtained from the entire …”
Section: Publication Bias: the "File Drawer Problem"mentioning
confidence: 99%